Risco moral em seguro saude: Uma análise para os Estados do nordeste utilizado estimadores de Matching por propensity score - Azevedo, Alana Katielli Nogueira (2008)
This dissertation analised the existence of moral hazard in the brazilian health system using anestimation of two propensity score matching models, one by stratification and the other one usinga kernel function. The variable of healthcare utilization selected was the medical visits and theanalysis was made considering the nine states of Northeast of Brazil. The results indicatedexistence of moral hazard for both stratification and kernel function estimation. For thestratification model the stimated value of the diference in medical visits stayed between 1,014 e 2,262 times, the state of Rio Grande do Norte had the greater diference. For the kernel functionmodel the stimated value of the diference in medical visits stayed between 0,866 e 2,242 times,the state of Maranhão had the smallest diference. So, individuals with health insurance use morethe healthcare than if they only have access to public services.